Polymer carriers for controlled fragrance release. (7th August 2020) - Wei, Min; Pan, Xi; Rong, Lin; Dong, Aijun; He, Yunlu; Song, Xuyan; Li, Junsheng
Abstract: Fragrance is a class of material commonly used in many consumer products such as food and tobacco. Since most of the fragrance is highly volatile, the successful use of fragrance in practical application requires effective preservation of fragrance with appropriate substrate material. As a low cost and versatile material, polymer holds great promise as a fragrance carrier. In this review, we summarize representative polymer carriers developed recently for sustained and controlled release of fragrance, which include natural polymers and novel synthetic polymers. The results summarized in this mini-review would shed light on the future design of advanced fragrance carrier for various applications.